Introducing the new bacterial branch of the RNase A superfamily. Issue 1 (2nd January 2018) - Cuthbert, Bonnie J.; Burley, Kalistyn H.; Goulding, Celia W.
ABSTRACT: Bovine pancreatic ribonuclease (RNase A) is the founding member of the RNase A superfamily. Members of this superfamily of ribonucleases have high sequence diversity, but possess a similar structural fold, together with a conserved His-Lys-His catalytic triad and structural disulfide bonds. Until recently, RNase A proteins had exclusively been identified in eukaryotes within vertebrae. Here, we discuss the discovery by Batot et al. of a bacterial RNase A superfamily member, CdiA-CT Ykris : a toxin that belongs to an inter-bacterial competition system from Yersinia kristensenii. CdiA-CT Ykris exhibits the same structural fold as conventional RNase A family members and displays in vitro and in vivo ribonuclease activity. However, CdiA-CT Ykris shares little to no sequence similarity with RNase A, and lacks the conserved disulfide bonds and catalytic triad of RNase A. Interestingly, the CdiA-CT Ykris active site more closely resembles the active site composition of various eukaryotic endonucleases. Despite lacking sequence similarity to eukaryotic RNase A family members, CdiA-CT Ykris does share high sequence similarity with numerous Gram-negative and Gram-positive bacterial proteins/domains. Nearly all of these bacterial homologs are toxins associated with virulence and bacterial competition, suggesting that the RNase A superfamily has a distinct bacterial subfamily branch, which likely arose by way of convergent evolution. Finally, RNase A interacts directly with the immunity protein of CdiA-CT Ykris, thus the cognate immunity protein for the bacterial RNase A member could be engineered as a new eukaryotic RNase A inhibitor.